Pendugaan Produksi Padi Menggunakan Citra Sentinel-2A di Kabupaten Tabanan - WIRANATHA, I MADE ALIT; NUARSA, I WAYAN; SARDIANA, I KETUT (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.1, Januari 2021, 2021)
Estimation of Rice Production Using Sentinel-2a Image in Tabanan Regency Rice is strategical commodities because rice is a primary food in Indonesia. Thus, the estimation of rice production becomes crucial to do before the time of harvest to determine the availability of food. The objectives of this study were (1) developing of estimation equation model using Sentinel-2A imagery, (2) estimating rice field production using Sentinel-2A imagery, and (3) testing the accuracy of rice production estimation results using images Sentinel-2A. The research area is located in Tabanan Regency. Analysis of the research is done by the analysis of the single band and vegetation indices of Sentinel-2A satellite imagery. Estimation model of rice production developed by finding out the relationship between the satellite imagery data and the rice production data. Finally, accuracy test of the rice production estimation model is done using t test and regression analysis. The result of the study shows that the Normalized Difference Vegetation Index (NDVI) has the best relationship with the rice age and then used for the rice production estimation. The equation of rice production estimation is y = 7,7429ln (x) + 11,147, where y is the rice production in ton/ha and x is the value of NDVI of Sentinel-2A imagery in rice age range of 57 to 67 day after transplanting. The results of the accuracy test showed that the model obtained is suitable for estimating rice production with the accuracy level of 84,59% and a standard error of estimated production of ± 0,7463 ton/ha. Based on the research results, it can be concluded that the Sentinel-2A satellite imagery can be used to estimate the rice production with the enough accuracy. The results are expected to be a reference in estimating rice production in Tabanan Regency.